2022
DOI: 10.1093/ofid/ofac010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin 6 Level and Nutrition Status as Potential Predictors of Clinical Leprosy Development Among Household Contacts in Endemic Areas

Abstract: Background Leprosy is a chronic infectious disease that can lead to severe life-long disabilities. Close contacts of leprosy patients have a higher risk of acquiring the disease. Nevertheless, there is a lack of reliable markers to predict Mycobacterium leprae infection. We aim to identify new potential markers for developing clinical leprosy among contacts. Methods Serum levels of IL-6, IL-8, IL-10, hemoglobin, ferritin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In endemic controls, the most age is 39.6 years. 5 The results also showed no significant relationship between age in the study subjects, which compared leprosy patients, household contacts, and endemic leprosy with increased IL-6 levels.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In endemic controls, the most age is 39.6 years. 5 The results also showed no significant relationship between age in the study subjects, which compared leprosy patients, household contacts, and endemic leprosy with increased IL-6 levels.…”
Section: Discussionmentioning
confidence: 73%
“…Most household contacts in Indonesia have been examined in several areas, namely in Bali, East Java, and Central Java; it was found that the average age range of household contacts of leprosy sufferers is 30-40 years old. [6][7][8][9][10][11][12] This study is not much different from a study conducted by Oktaria et al (2022), where household contacts of leprosy patients have an average age of 37.3 years. In endemic controls, the most age is 39.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening of household contacts with anti-PGL-I is well established in the literature and other biomarkers have been evaluated to assess the risk of developing the disease ( 6–10 ). Furthermore, neural thickening and/or qPCR of slit skin smear and skin biopsy show a significant association with neural damage and could be used as biomarkers to initiate the treatment in these asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of symptoms, M. leprae is replicating and invading the host tissues ( 5 ), and biomarkers for the infection as anti-phenolic glycolipid-I (PGL-I) IgM antibodies have been recommended to detect a risk of infection in asymptomatic patients, especially household contacts. Some studies have also suggested a relation between infection in these patients and other biomarkers such as IL-6 and nutritional status ( 6 ), serum levels of IgA antibodies against NDO-HSA ( 7 ), CCL2 chemokine associated with IFN-γ ( 8 ), and IgM profile against NDO-HSA, LID-1, and NDOLID antigens, and monocytes and CD4+ lymphocyte frequency ( 9 ), beyond arginase activity ( 10 ) as a protective marker against this infection.…”
Section: Introductionmentioning
confidence: 99%